A HISTORICAL PERSPECTIVE ON THE ECONOMIC POLICIES OF THE MUGHAL EMPIRE - Singh, Joginder (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper explores the multifaceted economic strategies employed by the Mughal rulers, focusing on land revenue systems, trade, industry, and agriculture. The study delves into the mechanisms of taxation, particularly the land revenue system introduced by Emperor Akbar, and its impact on the agrarian economy. Furthermore, it examines the empire’s extensive trade networks, both regional and international, which contributed significantly to its wealth and global influence. Additionally, the role of the Mughal court in fostering the arts, architecture, and industry is considered as part of a broader economic vision. The economic policies of the Mughal Empire, which flourished in the Indian subcontinent from the early 16th to the mid-18th century, played a pivotal role in shaping the region’s economic landscape. This historical perspective highlights the complexities of Mughal economic policies, emphasizing their long-lasting effects on the social and political fabric of India. Through an examination of historical records and scholarly interpretations, this paper aims to provide a nuanced understanding of the economic strategies that underpinned one of the most powerful empires in world history.